In vitro comparison of different carotid artery stents: a pixel-by-pixel analysis using CT angiography and contrast-enhanced MR angiography at 1.5 and 3 T - Lettau, Michael; Sauer, Annett; Heiland, Sabine; Rohde, Stefan; Reinhardt, Julia; Bendszus, Martin; Hähnel, Stefan (Neuroradiology, 2010)
Introduction: CT angiography (CTA) and MR angiography (MRA) are increasingly used methods for evaluation of stented vessel segments. The purpose of this study was to compare CTA, contrast-enhanced MRA (CEMRA) at 1.5 T, and CEMRA at 3 T for the visualization of carotid artery stents and to define the best noninvasive imaging technique for each stent. Methods: CTA and CEMRA appearances of 18 carotid artery stents of different designs and sizes (4.0 to 10.0 mm) were investigated in vitro. The profile of the contrast-to-noise ratio (CNR) of the lumen of each stent was calculated semiautomatically by a pixel-by-pixel analysis using the medical imaging software OSIRIS®. For each stent, artificial lumen narrowing (ALN) was calculated. Results: In all but one stents, ALN was lower on CEMRA at 3 T than at 1.5 T. With CEMRA at 3 T and at 1.5 T, ALN in most nitinol stents was lower than in the groups of stainless steel and cobalt alloy stents. In most nitinol stents, ALN on CEMRA at 3 T was lower than on CTA. In all stainless steel stents and cobalt alloy stents, ALN was lower on CTA than on CEMRA. With CTA and CEMRA, in most stents ALN decreased with increasing stent diameter. Conclusion: CTA and CEMRA evaluation of vessel patency after stent placement is possible, but considerably impaired by ALN. Investigators should be informed about the method of choice for every stent.